Planning Maine’s Energy Future - Silkman, Richard; Flumerfelt, John (Maine Policy Review, 1991)
Secure and reasonably priced energy supplies have always been vital to the welfare ofMaine’s economy and its people.Maineresponded to the energy shocks of the 1970s with important state policies, designed in large part to reduce dependence on foreign oil. John Flumerfelt and Richard Silkman of the State Planning Office provide for us an overview of Maine’s recent history of energy use and an analysis of both past and future energy policies in Maine. Two alternatives perspectives on energy policy are provided by Beth Nagusky of the Natural Resources Council of Maine and Matthew Hunter of Central Maine Power [this issue].